Maximal Feeding Depths of Walruses - Fay, F.H.; Burns, J.J. (ARCTIC, 1988)
Walruses (Odobenus rosmarus) feed mainly on benthic invertebrates in waters less than 80 m deep, and they have been presumed to be incapable of diving to greater depths. Reported here are seven walruses whose stomachs contained significant amounts of benthic sediments and food, some of which must have been ingested in waters more than 100 m deep. Walruses may be able to dive to depths much greater than 100 m, but they usually have little reason to do so, since their benthic prey are most abundant in shallower waters.Key words: walrus, Odobenus, diving, feeding, Bering Sea Mots clés: morse, Odobenus, plongée, alimentation, Mer de Bering